Using the ECERS to enhance teachers' understanding of the impact of classroom quality on children's development - Karim, Zinia Jesmin (BRAC University, 2010)
This thesis is submitted in partial fulfillment of the requirements for the degree of Masters of Science in Early Child Development, 2010.